2023
DOI: 10.1111/jftr.12525
|View full text |Cite
|
Sign up to set email alerts
|

Single and flourishing: Transcending the deficit narratives of single life

Abstract: From the couples‐centered perspective that has dominated public discourse and scholarly literature, the values and interests of coupled people are the implicit standard against which single people are judged, resulting in deficit narratives of single life. From that perspective, single people are “alone” and “unattached,” the important people in their lives are mere substitutes for a romantic partner, and their families, if recognized at all, are described as “alternative” family forms. From a singles‐centered… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 88 publications
(135 reference statements)
0
5
0
Order By: Relevance
“…Building on this, Beckmeyer and Jamison (2023) demonstrate that singlehood in young adulthood allows for exploration of identity through self-reflection, education, and relationships broadly when romantic relationships may be a barrier. DePaulo (2023) and Kislev and Marsh (2023) specifically discuss singlehood as a chosen identity, and Fitzpatrick (2023) distinguishes voluntary and involuntary singlehood. However, Bergström and Brée (2023) argue that singlehood should be approached as status rather than identity because there is not a singular understanding or definition of "single," as singlehood is a period of life and differs across the life course.…”
Section: A Call To Actionmentioning
confidence: 99%
See 1 more Smart Citation
“…Building on this, Beckmeyer and Jamison (2023) demonstrate that singlehood in young adulthood allows for exploration of identity through self-reflection, education, and relationships broadly when romantic relationships may be a barrier. DePaulo (2023) and Kislev and Marsh (2023) specifically discuss singlehood as a chosen identity, and Fitzpatrick (2023) distinguishes voluntary and involuntary singlehood. However, Bergström and Brée (2023) argue that singlehood should be approached as status rather than identity because there is not a singular understanding or definition of "single," as singlehood is a period of life and differs across the life course.…”
Section: A Call To Actionmentioning
confidence: 99%
“…Furthermore, a key task for future research is for more data collection efforts to include both retrospective and prospective measurement approaches to redefine singlehood (Mortelmans et al, 2023). A few authors (e.g., DePaulo, 2023;Ermer & Keenoy, 2023) address the importance of qualitative research in understanding the lived experiences and narratives of singlehood, and many authors cite work based on in-depth narrative interviews. Authors also acknowledge that even when attempting to define and conceptualize singlehood, it is often an elusive concept-one that varies within an individual over their lives, across individuals who would otherwise appear similar in terms of being single, and across contexts and time periods.…”
Section: A Call To Actionmentioning
confidence: 99%
“…They may also view other social relationships as supportive, even without being in a romantic relationship. Indeed, researchers have found that single adults tend to have a greater friendship network and perceive greater friend support than their romantically involved peers (e.g., DePaulo, 2014DePaulo, , 2023.…”
Section: Moderating Effect Of Romantic Importancementioning
confidence: 99%
“…Research on young adult singlehood has largely been framed from a deficit perspective (DePaulo, 2023). For example, scholars have described ways in which single young adults may miss out by not having romantic partners, highlighted negative feelings toward being single, and positioned being single as less desirable than having a romantic partner (Girme et al, 2016;Lehmann et al, 2015;Sharp & Ganong, 2011).…”
mentioning
confidence: 99%
“…Because romantic involvement appears to be a salient developmental task that may promote young adult well-being, being single during young adulthood has often been framed as costly for growth and development during this stage of the life course (e.g., Ta et al, 2017). However, some scholars have begun challenging the deficitperspective of singlehood (DePaulo, 2014(DePaulo, , 2023Pepping et al, 2018) by exploring how young adults' romantic beliefs and desires, personality characteristics, and life circumstances shape their experiences of being single and its connections with well-being (Beckmeyer & Cromwell, 2019;Beckmeyer & Jamison, 2023a;Girme et al, 2016;Lehmann et al, 2015;Sharp & Ganong, 2011;Watkins & Beckmeyer, 2023).…”
Section: Abstract Emerging Adulthood Romantic Development Singlehood ...mentioning
confidence: 99%